2020
DOI: 10.3390/md18040182
|View full text |Cite
|
Sign up to set email alerts
|

LC–HRMS and Chemical Derivatization Strategies for the Structure Elucidation of Caribbean Ciguatoxins: Identification of C-CTX-3 and -4

Abstract: Ciguatera poisoning is linked to the ingestion of seafood that is contaminated with ciguatoxins (CTXs). The structural variability of these polyether toxins in nature remains poorly understood due to the low concentrations present even in highly toxic fish, which makes isolation and chemical characterization difficult. We studied the mass spectrometric fragmentation of Caribbean CTXs, i.e., the epimers C-CTX-1 and -2 (1 and 2), using a sensitive UHPLC–HRMS/MS approach in order to identify product ions of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 30 publications
4
70
0
1
Order By: Relevance
“…In HRMS spectra ( Figure 1A Figure 1B and Figure S1, Table S1). As with CTX3C and CTX1B [17], the opening of the G-and H-rings allowed the formation of the ion at m/z 563.3220 followed by water losses at m/z 545.3115, m/z 527.3009, and m/z 509.2903, these fragments were also detected in [20] ( Figure 1B and Figure S1, Table S1). Table S1).…”
Section: Lc-hrms Analysis In Targeted Ms/ms Mode Of C-ctx1mentioning
confidence: 81%
See 1 more Smart Citation
“…In HRMS spectra ( Figure 1A Figure 1B and Figure S1, Table S1). As with CTX3C and CTX1B [17], the opening of the G-and H-rings allowed the formation of the ion at m/z 563.3220 followed by water losses at m/z 545.3115, m/z 527.3009, and m/z 509.2903, these fragments were also detected in [20] ( Figure 1B and Figure S1, Table S1). Table S1).…”
Section: Lc-hrms Analysis In Targeted Ms/ms Mode Of C-ctx1mentioning
confidence: 81%
“…Despite this, the applicability of HRMS has been demonstrated in particular for CTX1B and CTX3C as the main toxins responsible of CP in the Pacific Ocean, the fragmentation pathways have been identified, increasing the knowledge on how these complex toxins fragment in the mass spectrometer [17][18][19]. Recent studies published by Kryuchkov et al [20] reported strategies for the structure elucidation of Caribbean ciguatoxin analogues (C-CTX3 and C-CTX4).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous studies have shown the ability of Gambierdiscus to produce a wide variety of P-CTX analogs as well as their bioaccumulation at each trophic level, from herbivorous to carnivorous fish or marine invertebrates [28,92]. However, despite the identification of several C-CTX and I-CTX analogs in carnivorous fish and sharks [93][94][95][96][97][98][99][100], no study has yet been able to demonstrate the toxin production of C-CTXs or I-CTXs in Gambierdiscus.…”
Section: Discussionmentioning
confidence: 99%
“…Pacific ciguatoxins are the most numerous and well-characterised of the ciguatoxins and this group accounts for more than three quarters of the ciguatoxins that are known [4][5][6]. Four Caribbean ciguatoxins have been characterized-C-CTX-1 and C-CTX-2 are equilibrating lactols and C-CTX-3 and C-CTX-4 are diastereomers that arise by reduction of C-CTX-1/C-CTX-2 [7,8]. A further eight Caribbean ciguatoxins have been detected by mass spectrometry but have yet to be characterised and the structures of the six ciguatoxins-I-CTX-1-6-isolated from samples collected in the Indian Ocean have yet to be elucidated [6,9,10].…”
Section: Structures and Bioactivities Of The Ciguatoxinsmentioning
confidence: 99%